Pullout behaviour of anchor block under saturated and unsaturated soil conditions / Adnan Derahman - Derahman, Adnan (Institute of Graduate Studies, UiTM, 2012)
There have been many cases of wall failure by bulging. The potential causes of this type of wall failure are might due to the over-estimate the shear strength at the lower part of wall, the influence of a hydrostatic pressure at lower part of the retaining wall and the soil in the retaining wall transformed from unsaturated to saturated condition. This is anticipated to be the cause of wall bulging. This illustrates the importance of applying the right shear strength which can be achieved through the curved surface envelope shear strength model. This also gives the implication that the application of the curved surface envelope shear strength model will be more conservative than the Terzaghi’s, 1936 model. This thesis presents the results of an investigation into soil-reinforcement interactions under saturated and unsaturated conditions by means of pullout tests. Especially for this purpose, an apparatus able to contain 2 cubic meter sample of backfill material was designed by the author in order to perform real scale tests.